2004
DOI: 10.1002/mrm.20063
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of simulated short echo time 1H human brain spectra by LCModel and AMARES

Abstract: LCModel and AMARES, two widely used quantitation tools for magnetic resonance spectroscopy (MRS) data, were employed to analyze simulated spectra similar to those typically obtained at short echo times (TEs) in the human brain at 1.5 T. The study focused mainly on the influence of signal-to-noise ratios (SNRs) and different linewidths on the accuracy and precision of the quantification results, and their effectiveness in accounting for the broad signal contribution of macromolecules and lipids (often called th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
119
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 24 publications
9
119
0
Order By: Relevance
“…As indicated earlier, Voigt lineshape is a better approximation than Lorentzian or Gaussian alone [18]. It is also worth pointing out that Kanowski et al [46] have also observed lower Cho values with AMARES compared with the LCModel. The concept of using ANN for the analysis of MRSI is not new.…”
Section: Discussionmentioning
confidence: 60%
“…As indicated earlier, Voigt lineshape is a better approximation than Lorentzian or Gaussian alone [18]. It is also worth pointing out that Kanowski et al [46] have also observed lower Cho values with AMARES compared with the LCModel. The concept of using ANN for the analysis of MRSI is not new.…”
Section: Discussionmentioning
confidence: 60%
“…The free induction decays were analyzed by use of the LCModel software 23 (downloadable test version at: http://s-provencher.com), which simulates the spectra with a linear combination of model spectra and is considered to be the most suitable tool for analyzing short-TE spectra. 24 Baseline correction was performed, including macromolecules. The Cramer-Rao lower bounds indicated by the program were used to measure the quality and reliability of the 1 H spectroscopic data, rejecting data with values below 20%.…”
Section: Processingmentioning
confidence: 99%
“…Clinicians and scientists who have a more intimate understanding of MRS utilize many methods for quantification of in vivo MR spectra [117,[307][308][309][310][311][312][313][314]. A relative calculation can be performed in which metabolite peaks of interest are integrated and are normalized to a metabolite that is assumed to be unchanged by the disease.…”
Section: Quantification and Interpretation Of Spectramentioning
confidence: 99%